Sistem Pendukung Keputusan Untuk Mempermudah Kinerja Dalam Proses Penerimaan Beasiswa Menggunakan Metode SAW (Simple Additive Weighting) Berbasis Web (Studi Kasus: SMAS Empat Lima 1 Babat) - Muhammad Rizki Wicaksono; Setiabudi Sakaria; Chaulina Alfianti Oktavia (J-INTECH ( Journal of Information and Technology), 2020)
The large number of students applying for Achievement scholarships and BKSM (Special Assistance for Poor Students) at SMAS Empat Lima 1 Babat makes the performance of schools still not optimal. That is because all the inputting processes for receiving scholarships are still manual. Decision support systems are useful for expanding decision makers' ability to process data or information and can help solve problems, especially in a variety of very complex and unstructured issues. One method in a decision support system is SAW (Simple Additive Weighting), the method is able to process the scholarship selection results automatically through a system that has been created so that the results are faster and more accurate. The results showed that the Decision Support System in the Scholarship Acceptance Process that used the SAW method succeeded in determining the order (priority) of students who were eligible and eligible to receive scholarships using the SAW method. The highest final grades processed by Decision Support System are students who are recommended and are eligible to receive scholarships, while students with the lowest final grades are students who are not recommended or are not eligible to receive scholarships. In addition, the use of a data input web program is more effective and efficient when compared to using Microsoft Excel because the data entered has been processed by the system.